Adaptação transcultural e validação do conteúdo do “formulário de avaliação do desenvolvimento da competência de autocuidado de pessoas com ostomias de eliminação intestinal” para o contexto brasileiro - Claudiomiro da Silva Alonso (2021)
Introduction: The care of people with an intestinal ostomy is consolidated as a complex process, as it generates changes at all levels of their life, especially in the need for self-care. Self-care for people with intestinal ostomies is still a challenge for patients and health professionals. When self-care skills are not developed in a correct and temporal manner, complications can arise, increasing costs for health services and decreasing the quality of life of people with intestinal ostomies. In Brazil, we still do not have a validated instrument that assesses these people's self-care skills. On the international scene, there is a “form for evaluating the development of self-care competence of people with intestinal elimination ostomies”, created in Portugal and disseminated in Europe, which is considered by psychometrists as a coherent, relevant and specific technology. Objective: to perform crosscultural adaptation and content validation of the “form for evaluating the development of selfcare competence of people with intestinal elimination ostomies (CAO-EI: ESEP)” for the Brazilian context. Method: this is a methodological study conducted using a quantitative approach, which performed the cross-cultural adaptation and content validation of the CAOEI: ESEP. Preliminarily, the authorization of the authors and the institution holding the copyright was requested. The study followed the steps of translation, synthesis, backtranslation, analysis by a committee of judges, pre-test and adaptation review committee. Data collection was performed using the digital Google forms platform. The committee of judges was divided into two groups: specialists and experts. The interdisciplinary specialist core was composed of nine members, who evaluated the form in search of idiomatic, conceptual, semantic and experiential equivalence. The expert committee was composed of 20 stomal therapists from the five regions of the country, who assessed the psychometric property of content validity, based on behavioral criteria, simplicity, clarity, relevance and typicality. The pre-test was carried out with 40 nurses who evaluated the instrument for clarity of items, relevance to the context and conceptual relevance. The frequencies and percentages of agreement and the content validity index were used as analytical models. Results: after replacing, inserting, modifying and excluding terms and expressions, the form obtained equivalence in the semantic, idiomatic, conceptual and experiential domains, as evidenced by a percentage of agreement > 85% in all items. After two rounds of evaluation by the expert committee, the content was considered adequate, obtaining a CVI close to 1.0 in most of the items evaluated. Conclusion: cross-cultural adaptation was the process used to obtain cultural equivalence between the Portuguese and Brazilian versions of the CAO: EI – ESEP, which was confirmed by the recurrent frequencies of adequate agreement. The psychometric property of content validity was achieved after two evaluation cycles carried out by experts representing the five regions of Brazil, which allowed the construction of content that respects the cultural plurality originating in the regionality of the Brazilian territory. This study contributes to the transformation in the way of evaluating people with intestinal elimination ostomies, since, in its scope, it praises the systematic and individualized assessment of selfcare, offering representative and understandable content for nurses who will be able to use the instrument in the development of care in the future.